Hak Waris pada Orang dengan Orientasi Gender Biner - Ahdah, Ina Tasya Aunil; Ahmad, Muh. Jufri (CV. Era Digital Nusantara, 2025)
Certain individuals experience gender identities that do not align strictly with being male or female. These individuals may identify as a blend of both male and female, as different genders at varying times, as having no gender at all, or as questioning the traditional binary understanding of gender. Terms commonly used to describe these identities include